2017
DOI: 10.7717/peerj.4021
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of cross neutralizing human monoclonal antibody against 4 serotypes of dengue virus without enhancing activity

Abstract: BackgroundDengue disease is a leading cause of illness and death in the tropics and subtropics. Most severe cases occur among patients secondarily infected with a different dengue virus (DENV) serotype compared with that from the first infection, resulting in antibody-dependent enhancement activity (ADE). Our previous study generated the neutralizing human monoclonal antibody, D23-1B3B9 (B3B9), targeting the first domain II of E protein, which showed strong neutralizing activity (NT) against all four DENV sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The variable genes of the heavy (VH) and light (VL) chains of the B3B9 HuMAb were amplified separately via polymerase chain reaction (PCR) from hybridoma cells [22], and cloned into plasmid containing antibody constant region of pQCX plasmid backbone (Pitaksajjakul et al, 2014;Injampa et al, 2017). Antibody mutations were performed over the Fc portion of the heavy chain plasmid regions at positions 234 and 235 from leucine (L) to alanine (A) (L234A, L235A [LALA]) by site-directed mutagenesis with the In-Fusion Cloning System (In-Fusion® HD Cloning Plus; Clontech Laboratories Inc., Shiga, Japan) based on the manufacturer's protocol [13].…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable genes of the heavy (VH) and light (VL) chains of the B3B9 HuMAb were amplified separately via polymerase chain reaction (PCR) from hybridoma cells [22], and cloned into plasmid containing antibody constant region of pQCX plasmid backbone (Pitaksajjakul et al, 2014;Injampa et al, 2017). Antibody mutations were performed over the Fc portion of the heavy chain plasmid regions at positions 234 and 235 from leucine (L) to alanine (A) (L234A, L235A [LALA]) by site-directed mutagenesis with the In-Fusion Cloning System (In-Fusion® HD Cloning Plus; Clontech Laboratories Inc., Shiga, Japan) based on the manufacturer's protocol [13].…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Our previous study revealed the glycosylation of human monoclonal antibody against DENV (N297Q-B3B9) [13]. This cross-neutralizing HuMAb is targeted to domain II of the envelope proteins, which is a major target epitope of human antibodies for neutralizing and enhancing activity [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of serotype-specific mAbs or high dose administration of cross-reactive mAbs has demonstrated reduced risk of ADE in vitro and in animal models. Further, antibodies with modifications in the Fc region such as deletion of nine amino acids (at positions 231-239) in the N terminus, mutation of asparagine to glutamine at position 297 (N297Q), or mutation of leucine to alanine at positions 234 and 235 (LALA mutants) have also shown reduced risk of ADE and exhibited prophylactic and therapeutic efficacy in animal models (Balsitis et al 2010;Shi et al 2016;Xu et al 2017;Injampa et al 2017;Lu et al 2018). Fc region modifications that extend the antibody half-life also help minimize ADE by maintaining the mAbs at high levels.…”
Section: Implications For Dengue Therapeuticsmentioning
confidence: 99%
“…Three domains (EDI, EDII, and EDIII) are formed in the spatial structure based on the determined crystal structure of the E protein. Among these, EDII, which is located at the amino terminus of the E protein, contains a fusion peptide structure that mediates the fusion of the virus and the target cell (fusion loop, 98-110 AA) (6). Meanwhile, EDIII facilitates the adsorption of viruses to target cells and is considered to contain the receptor binding region as well as the most important neutralizing epitope (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%